Social Murder and Other Shortcomings of Conservative Economics - Lewchuk, Wayne (Labour / Le Travail, 2009)
The article reviews the book, "Social Murder and Other Shortcomings of Conservative Economics," by Robert Chernomas and Ian Hudson.
Keywords: BOOKS -- Reviews; CHERNOMAS, Robert; HUDSON, Ian; Nonfiction; SOCIAL Murder & Other Shortcomings of Conservative Economics (Book); SOCIOECONOMICS